EXPECTATION BASED REWARD SYSTEM FOR REDUCING EMPLOYEES’ TARDINESS - Antonius Edwin Sutikno (Universitas Airlangga, 2019)
Background: Motivating employees can improve their morale and job satisfaction. Work motivation has a positive effect on work discipline and employee’s performance. Organizations provide reward to their employee to motivate improvement in performance. On the other hand, lack of motivation will result in tardiness. A monthly report of one clinic in Surabaya, for example, shows alarming level of personnel’s tardiness from July to October 2014, with the mean score of 88.85 minutes compared to the standard tolerance of tardiness 15 minutes per day.Aims: This study aims at formulating appropriate recommendations of reward system to reduce employee’s tardiness at one clinic in Surabaya.Methods: This is a quantitative analytical study with a cross-sectional design and observation method. The research samples are 17 employees of the clinic chosen using purposive samplingResults: Results show that 82.35% of employees chose additional incentives as a reward if they do come on time. The majority of employees chose a range of Rp. 51,000 to Rp. 70,000 as the typical amount of incentive. Not all employees agreed to the implementation of punishment system. The reward system is applied when the employees have good attendance record in one month.Conclusions: Extra incentive provides good motivation for employees to deliver proper healthcare in time. The application of reward system from November 2014 to January 2015 gave a positive result in terms of decreasing the number employees who come late to work. Healthcare providers should evaluate employees’ performance and implement reward system to increase the quality of human resource.Keywords: Tardiness, Punishment, Reward.